Effectiveness of corticosteroid injection vs platelet rich plasma (PRP) injection in the treatment of plantar fasciitis - Nepal , Santosh; Kumar Gupta, Mithilesh; Panthee, Rajan; Kafle, Gokul; Kumar Sah, Raj (Birat Journal of Health Sciences, 2024)
Introduction: Plantar fasciitis is one of the most common causes for inferior heel pain in adults. Many noninvasive and invasive treatment modalities are available for its treatment. Local injection of corticosteroid and Platelet-rich plasma (PRP) is usually used in the treatment of chronic plantar fasciitis not responding to noninvasive conservative treatments. Objectives: To compare the efficacy of local injection of corticosteroids and platelet rich plasma (PRP) in the treatment of plantar fasciitis. Methodology: Patients diagnosed as plantar fasciitis and treated conservatively for at least 3 months and had no response to conservative treatment modalities were involved in this study and randomly allocated into 2 groups of 38 each (Group A and Group B). Patients were treated with local corticosteroid injection in group A and autologous PRP injection in group B. Clinical assessment was done prior to the injection and at 3 weeks and 3 months following the injection, which included visual analog pain scale (VAS), subjective rating using the modified Roles and Maudsley score (MRMS), functional outcome score by the Foot function Index (FFI). Results: The mean age, sex and body mass index was comparable for both groups. Postinjection, there was significant improvement (p < 0.05) of visual analog score (VAS), modified Roles and Maudsley score (MRMS), Foot Function Index in both the groups. However, there was no significant difference (p > 0.05) in improvement of VAS, MRMS and FFI when compared between the 2 groups. Conclusion: This study revealed that the treatment of plantar fasciitis with steroid or PRP injection was equally effective in patients who do not respond to conservative treatment.